The Pendulum of Positivism - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2004)
This article discusses the technocratic collision of sociology. Sociology is a discipline with a strong commitment to tradition of positivism. On the one hand, sociology has developed on the premises of scientific methodology, making it the technical imperative of social investigation, using it to ground her cumulative knowledge claims. It was the fascination with the apparently relentless success of positivistic sociology that prompted the empiricist knowledge to dislodge other forms of knowledge.On the other hand, the turn of latter-day sociological inquiry, as compared with the traditional attempt to apply the standarts of positivism, shows that under the new historical and practical perspective the sociology undergoes a discursive reframing. The argument here is that the limits of sociology as a discipline stem mainly from reductive methodological attempts. The growing interest in culture of science provides an interesting pluralist perspective. The better understanding of diverse theoretical and empirical approaches can provide the base for the creation of new reflexive sociological trends.
Keywords: sociology; positivism; methodology; reflexivity